A Staged Treatment Algorithm for the Management of Severe Charcot Hindfoot Arthropathy, using Tibiotalocalcaneal Arthrodesis with Femoral Head Allograft. Issue 4 (22nd October 2020) - Khwaja, Ansab M.; Manoharan, Aditya; Khwaja, Ansab M.; Sorenson, Jacob; Etebari, Cyrus V.; Latt, L. Daniel
Category: Diabetes; Ankle; Diabetes; Hindfoot Introduction/Purpose: Charcot neuroarthropathy of the hindfoot (Brodsky type 2 and 3) can involve significant talar collapse / bone loss leading to hindfoot instability, the goal of treatment to create a stable plantigrade shoeable ulcer and infection free foot. This can often be achieved with tibiotalocalcaneal (TTC) arthrodesis but a plantigrade foot can be challenging in setting of significant talar bone loss. Structural allograft has been used in association with TTC fusions in a number of settings but not explored in the treatment of charcot hindfoot. The goal of this study was to examine the outcomes of structural allografting combined with TTC arthrodesis for the treatment of charcot hindfoot. Methods: Retrospective review of all patients treated at our institution with a Brodsky type 2 or 3 was performed over a five year period from 2014 - 2019. We identified twenty-two patients, 12 males and 10 females with a mean age of 57 years. All underwent surgery by the senior author, a fellowship trained foot and ankle orthopedic surgeon. Patients with infection were treated with antibiotics and a Taylor spatial frame prior to definitive stabilization. Non-infected patients were either placed in a total contact cast (TCC) if they were in active charcot or underwent primary charcot reconstruction. If after initial treatment patients had a plantigrade foot, they were placed in stiff soled rocker bottom shoe with custom accommodative insoles. Patients who did not have a plantigrade foot underwent TTC arthrodesis to achieve this. Femoral head allograft was used if excessive talar bone loss or collapse of the hindfoot was noted. Results: At final follow up 13 patients (59%) of the cohort achieved grade 1, an infection and ulcer free plantigrade foot that was able to fit in a shoe. 7 (32%) of patients achieved grade 2, a plantigrade foot in brace, and 2 (9%) achieved level 3 a plantigrade foot. No patients in this cohort underwent amputation. Average duration of treatment until final status was 18 months (minimum 2, maximum 37), number of interventions 3.9 (minimum 1, maximum 10). Of the twelve patients who required allograft, they averaged 4.25 interventions and average time of 17.6 months until final status. Of those who did not require allograft, they averaged 3.4 interventions with follow up of 11.9 months. Conclusion: Our data suggests that patients with Brodsky type 2 and 3 charcot arthropathy of the ankle and hindfoot even with infection can be successfully treated with staged treatment. This includes external fixation and infection management, followed by tibiotalocalcaneal intramedullary nail fixation with or without femoral head allograft to allow for a plantigrade foot and weight bearing in a stiff soled rocker bottom shoe. Further study is needed to determine long term outcomes and relapse rates.